Prevalence of adjacent-level fractures after osteoporotic vertebral compression fractures: a prospective non-randomized trial comparing percutaneous vertebroplasty with conservative therapy: Pogostost zlomov sosednjih vretenc po osteoporotičnem zlomu vretenca: prospektivna, ne-randomizirana primerjava med perkutano vertebroplastiko in konzervativnim zdravljenjem - Movrin, Igor (Acta Medico-Biotechnica, 2021)
Purpose: The purpose of this prospective non-randomized study was to analyze the prevalence and possible risk factors of adjacent-level fractures comparing percutaneous vertebroplasty (PVP) with conservative therapy.Methods: Consecutive patients satisfying the inclusion criteria of acute vertebral fracture pain (occurring within 1-6 weeks of the event and not relieved by oral analgesia) and imaging criteria of acute fracture activity were enrolled. All patients meeting the inclusion criteria were offered PVP. Patients who declined PVP and agreed to longitudinal evaluation were treated conservatively and constituted the control group.Results: In 2 of 27 patients (7.4%) treated with PVP and in 10 of 61 patients treated conservatively (16.4%), adjacent-level fractures occurred within 1 year. The degree of local kyphosis and bone mineral density (BMD) were identified as possible predictive factors for adjacent-level fractures.Conclusion: These results indicated that PVP carries a low risk of adjacent-level fractures. Lower BMD values and altered biomechanics in the treated area of the spine due to resistant kyphosis are possible predictive factors for adjacent-level fractures. A positive effect of PVP over conventional treatment was observed upon reduction of the prevalence of adjacent-level fractures, vertebral morphology, and pain reduction.
Keywords: Adjacent vertebral fracture; Vertebroplasty; Comparative analysis; Local kyphosis; Bone mineral density